Museum Monumentation: a Fight for R.A Kartini Identity as a Tourist Attraction - Yuliawan, Rahmat; Aly, M. Nilzam; Kristanto, Damar; Hamid, Nur (International Journal of Psychosocial Rehabilitation, 2020)
This article outlines monumentation of R.A Kartini, a national hero, situated in two cities. R.A Kartini is simply immortalised to become museums’ identity with a twin name, but in different areas and with different management. As a hero, she has monumented on a national scale in every 21stApril known as Kartini Day. Researchers relied on data taken from observation process, in depth interview, and a questioner given to 100 respondents. An outcome of the analysis reveals that monumentation process towards R.A Kartini was just restricted to historical narration and normative activity conducted all at once on Kartini Day. As a result, there isa bias for the identity of “Kartini City” since people do not even exactly recognize where is the location of R.A Kartini museum as a tourism object. Concisely, we submitthat the monumentation process can be directed to a clear, focus, and specific territorial identity which positively affects the number of museum visitors as a monumentation tangible.